La Vegetazione del Parco del Conte (Ruvo di Puglia) - Scaramuzzi, Franca; Lorito, Fernanda (Giornale botanico italiano, 1953)
Summary The flora of a Quercus pubescens wood, near Ruvo di Puglia, has been studied. The presence of Pirus amygdaliformis, and of various weeds, together with the disappearence of some species like Bivonaea albiflora, indicate a certain amount of degradation due to grazing and cutting. The biological spectrum shows a noticeable abundance of therophytes (45%). The mixture of typical mediterranean «maquis» plants and of more mesophilous species suggests that at Ruvo the basal Quercus Ilex horizon finds its ecological boundary, Q. pubescens substituting green oak and decidous plants outbalancing evergreens.
doi: 10.1080/11263505309432122
Keywords: degradation; ecological boundary; floral composition; Mediterranean maquis; Ruvo di Puglia (PG)